مزدور کے حقوق، شریعت اور پاکستانی آئین کی نظر میں ایک تحقیقی وتنقیدی مطالعہ - Fazal e haq; Lutfullah Saqib (Pakistan Journal of Islamic Research)
Labors are, of course, the backbone of every economy whether under developing, developing or developed. Owing to this fact, a vital importance is supposed to be given to the labors and their rights.  However, contrary to this, labors are deprived badly from their rights, ironically, even by the developed countries.  While recognizing this situation, though latter on, various laws, rules and regulations are added to the legal spectrum of various countries in order to give quality life standards to the labors and their families.  Pakistan, too, has taken some measures in this regard through the introduction of various laws related to uplift of labors- by one way or another. Sharī’ah (Islamic Law), unlike the conventional system, has envisaged such rights from the very beginning.  Because of this reason, the Holy Qur’ān, Hadīth and classical Muslim fuqahā (jurists) have discussed labors’ rights with minute details.  These rights can be broadly divided into moral and substantial rights – a comprehensive division of rights that cannot be found in any other legal system. The present research endeavor, therefore, aims to critically analyze and compare the labors’ rights in Pakistan with those offered by Islamic law since long.  Findings show, with solid evidences, that majority of such rights (given by Islamic law to the labors) are inculcated in the legal system of Pakistan – mainly being an Islamic state. However, still there is room for further improvement. The present work, therefore, advances suggestions in this regard, too. Being a qualitative research, content analysis technique is followed in the present work for the investigation of the issue.